Germany’s Internationalization Strategy: Staying Open While Others Close Doors - Morris-Lange, Simon; Schueller, Jessica (International Higher Education, 2025)
<h3 id="germanys-20242034-internationalization-strategy-diverges-notably-from-the-restrictive-study-migration-policies-adopted-by-other-leading-destination-countries-while-germany-has-historically-followed-a-distinct-less-marketized-approach-to-international-education-it-is-not-immune-to-global-market-disruptions-salient-risks-like-overrecruitment-insufficient-oversight-and-political-complacency-could-weaken-germanys-internationalization-efforts-if-not-addressed-in-the-years-ahead" data-pm-slice="1 1 []">Germany’s 2024–2034 internationalization strategy diverges notably from the restrictive study-migration policies adopted by other leading destination countries. While Germany has historically followed a distinct, less marketized approach to international education, it is not immune to global market disruptions. Salient risks, like overrecruitment, insufficient oversight, and political complacency, could weaken Germany’s internationalization efforts if not addressed in the years ahead.